2016
DOI: 10.1371/journal.pone.0161704
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin Promotes Translocation of Glucose Transporter 4 in Muscle of Mice through Activation of Insulin and AMPK Signaling Pathways

Abstract: Procyanidins are the oligomeric or polymeric forms of epicatechin and catechin. In this study, we isolated and purified dimer to tetramer procyanidins from black soybean seed coat and investigated the anti-hyperglycemic effects by focusing on glucose transporter 4 (GLUT4) translocation and the underlying molecular mechanism in skeletal muscle of mice. The anti-hyperglycemic effects of procyanidins were also compared with those of monomer (−)-epicatechin (EC) and major anthocyanin, cyanidin-3-O-β-glucoside (C3G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 55 publications
3
45
0
Order By: Relevance
“…The results of the present study demonstrated that C3G induced similar hypoglycemic and hypolipidemic effects as SBp containing comparable amount of C3G in HFHS diet-induced insulin resistant mice. The ndings of the present study are consistent with the previous studies on the effects of Saskatoon berry and C3G in glucose and lipid metabolism reported by our and other groups [11,20,23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study demonstrated that C3G induced similar hypoglycemic and hypolipidemic effects as SBp containing comparable amount of C3G in HFHS diet-induced insulin resistant mice. The ndings of the present study are consistent with the previous studies on the effects of Saskatoon berry and C3G in glucose and lipid metabolism reported by our and other groups [11,20,23].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies demonstrated that C3G increased the translocation of glucose transporter-4 in skeletal muscle through the activation of insulin and AMP protein kinase pathway in mice [20]. C3G also augmented glucose-induced insulin secretion in INS-1E pancreatic β-cells and glucose uptake in HepG2 hepatocytes [21].…”
Section: Discussionmentioning
confidence: 86%
“…Phenolic compounds influence on hepatic GLUT4 level and/or activity has been so far scarcely evaluated, but recently Doan et al reported results of in vivo studies, where elevated hepatic GLUT4 mRNA levels were observed after the treatment of mice with gallic acid (2015). Independently, Ashida's team observed GLUT4 translocation after treatment of mice with dimer to tetramer procyanidins from black soybean seed coat and this effect was accompanied by AMPK activation (Yamashita et al, 2016). Other studies proved that the EGCG activation of AMPK was mediated by the Ca 2+ /calmodulin-dependent protein kinase kinase (CaMKK) dependent on ROS production (Collins et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that these fruits are a rich source of polyphenolic compounds (mainly catechins and procyanidin oligomers) possessing numerous biological activities (Strugała et al, 2016;Tarko et al, 2014;Bahadoran et al, 2013;Lewandowska et al, 2013;Gorlach et al, 2011;Stręk et al, 2007), we hypothesized that JQ extract can also activate AMPK. Recent reports evidenced black soybean seed coat and grape seed procyanidins as the agents responsible for AMPK activation and glucose uptake in mice and rats (Yamashita et al, 2016;Crescenti et al, 2015;Kurimoto et al, 2013). However, to the best of our knowledge, there are no earlier reports on Japanese quince polyphenols influencing glucose metabolism, thus the aim of the study was to test JQ effect on the AMPK activation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using extracts from plants have shown potential in improving diabetes following a significant improvement in glucose uptake [5][6][7][8][9]. Most of these plants have been reported to contain polyphenols as one of their active principles and recent reports also suggest the antidiabetic property of phenolics compounds [10,11]. α-glucosidase is the enzyme that catalyzes the key step of carbohydrate digestion and glucose release.…”
Section: Introductionmentioning
confidence: 99%